Bulgaria : Piloting Statistical Models for Estimation of Schools’ Value-Added Using the Results from the National Assessments - Danchev, Plamen (World Bank, Washington, DC, 2016)
The objective of this report is to document the process and summarize the results from the second phase of the pilot implementation of statistical models for measuring the value-added of Bulgarian schools through analysis of the national student’ assessments results. This report presents the technical aspects of the pilot and the key outcomes in terms of value-added measure for each of the schools included in the analysis. It is intended to ensure the institutional memory for the pilots and to stimulate the discussions at technical level among experts and decision makers at the Ministry of Education and Science (MES), focusing on the relevance and applicability of the piloted statistical models, in the context of Bulgaria student assessment framework, and given the available data. The report documents all the data processing, adjustments, and procedures run as part of the school value added modeling.